Photography as Visual Communication Media in MSME Product Promotion - Hidayat, Taopik; Sari, Maya Purnama (Capture : Jurnal Seni Media Rekam, 2024)
Micro, Small, and Medium Enterprise (MSME) are one of the key sectors supporting Indonesia's economy. This study aims to analyze the role of photography as a medium of visual communication in the promotion of MSME products. The research employs a qualitative descriptive method, with the object of study focusing on product photographs uploaded on the social media platform Instagram. The results indicate that photography serves as an effective tool for creating compelling visual representations in the promotion process of MSME products. Attractive product visuals through photography can increase consumer interest and broaden audience reach. Consequently, utilizing photography in promotional strategies enhances marketing effectiveness and supports MSMEs in building product image and competitiveness in the digital marketplace.